The Golden Halo and Political Transitions - Toke Aidt; Facundo Albornoz; Martin Gassebner (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
In this paper we analyze the role of the IMF and the World Bank in triggering changes in the political regime, i.e., democracy and autocracy. We develop a theoretical model which predicts that anticipation of financial flows from international financial institutions may trigger political regime changes which would not take place otherwise. We test the implications of our model empirically and find support both for the role of perfectly foreseen IMF and World Bank programs and of the history of previous World Bank programs. The magnitude of this effects is quite substantial.
Keywords: 330; political transitions; democracy; autocracy; political instability